Agricultural research for development : the Namulonge contribution - Arnold, M. H.; Cotton Research Corporation (Cambridge ; New York : Cambridge University Press, 1976)
This is a case study of agricultural research in relation to development. Although it primarily deals with the Namulonge Cotton Research Station, it also discusses the wide implications of the ways in which agricultural research can best be organized. A review is presented of the contributions to agricultural science in the main disciplines: agrometeorology, soil productivity, crop physiology, entomology, plant pathology and plant breeding. A special chapter is devoted to incorporating genetic resistance against pests and diseases into new varieties. The final chapter discusses the problem of applying research results to local agriculture.
At head of title: Cotton Research Corporation.
Includes indexes.
Bibliography: p. [325]-343.
lje 14/06/17
Loans
Keywords: Agriculture; Cotton